2021
DOI: 10.1101/2021.04.12.21255327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on health service utilisation in Sierra Leone

Abstract: Introduction: The COVID-19 pandemic has adversely affected health systems in many countries, but little is known about effects on health systems in sub-Saharan Africa. This study examines the effects of COVID-19 on health service utilisation in a sub-Saharan country, Sierra Leone. Methods: Mixed-methods study using longitudinal nationwide hospital data (admissions, operations, deliveries and referrals), and qualitative interviews with healthcare workers and patients. Hospital data were compared across Quarters… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Our study indicates that hospital admissions fell dramatically with the onset of the COVID-19 pandemic for all of nine non-COVID-19 diseases investigated, including infectious and parasitic diseases, neoplasms, mental and behavioral disorders, diseases of the nervous system, diseases of the circulatory system, diseases of the respiratory system, diseases of the digestive system, diseases of the genitourinary system, and pregnancy, childbirth and the puerperium. Our results demonstrate a sharp and significant decrease in hospitalizations in the first month after the COVID-19 outbreak, which is consistent with previous studies in other countries [ 6 8 , 16 , 17 ]. A recent WHO survey looked at the extent of the disruption of services for the prevention and treatment of non-communicable diseases [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study indicates that hospital admissions fell dramatically with the onset of the COVID-19 pandemic for all of nine non-COVID-19 diseases investigated, including infectious and parasitic diseases, neoplasms, mental and behavioral disorders, diseases of the nervous system, diseases of the circulatory system, diseases of the respiratory system, diseases of the digestive system, diseases of the genitourinary system, and pregnancy, childbirth and the puerperium. Our results demonstrate a sharp and significant decrease in hospitalizations in the first month after the COVID-19 outbreak, which is consistent with previous studies in other countries [ 6 8 , 16 , 17 ]. A recent WHO survey looked at the extent of the disruption of services for the prevention and treatment of non-communicable diseases [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Healthcare utilization has repeatedly been observed to decrease during the COVID-19 pandemic [ 16 , 17 ]. Iran, as one of the countries with a high incidence of COVID-19, was found to be similarly affected, with steep reductions in the rate of hospitalizations, particularly early in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we document important declines in the use of health services during the first wave of the pandemic in Kinshasa, mostly notably in the parts of the city that were subject to lockdown. A number of recent preprinted studies have also begun to document similar effects observed in other SSA countries, including in Sierra Leone, 37 where hospital services were observed to have declined, and in Kenya. 38 More attention needs to be paid to ensuring the continuity of essential health services during outbreaks, especially during lockdown policies like the ones implemented in Gombe during the early phase of the pandemic.…”
Section: Discussionmentioning
confidence: 76%